Exploring the dynamics of dragon fruit production and its constraints in southern states of India - Akhil, N K; Prahadeeswaran, M; Shivakumar, K M; Sivakumar, V; Selvi, R G (Plant Science Today, 2025)
Dragon fruit, or pitaya, has become famous owing to its unique look, health advantages, and resilience to diverse climates, rendering it especially appropriate for Southern India. This study investigates the economic feasibility and production challenges of dragon fruit farming in Andhra Pradesh, Karnataka, and Tamil Nadu in 2024. Financial assessments using net present value (NPV), benefit-cost ratio (BCR), and internal rate of return (IRR) indicate that dragon fruit farming is profitable in these states, with Andhra Pradesh and Karnataka showing better financial outcomes compared to Tamil Nadu. Garrett's ranking technique was employed to identify and rank the production and marketing constraints. Key production challenges in Tamil Nadu and Andhra Pradesh include the high cost of installation materials and insufficient technical support, while Karnataka primarily faces a shortage of skilled labor. On the marketing front, the absence of adequate cold storage facilities and high transportation costs pose significant hurdles across all states. The findings highlight the need for targeted solutions, such as improving access to affordable installation materials, upgrading cold-storage infrastructure, and implementing training programs for farmers. Addressing these challenges can enhance the profitability and sustainability of the dragon fruit industry in Southern India.